Is Switzerland an interest rate island after all? Time series and non-linear switching regime evidence - Lars P. Feld; Ekkehard A. Köhler (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2015)
Has the 'Swiss interest rate anomaly' persisted after the financial crisis? Regarding the hypothesis that the Swiss interest rate anomaly results from systemic risk anticipation, we discuss whether Switzerland remains an interest rate island in the wake of the financial crisis. We find evidence for the demise of the interest rate bonus of the Swiss franc (CHF) vis-à-vis the Euro (EUR) after the Swiss National Bank (SNB) started to advocate an exchange rate floor with the Euro. After the compression of the bonus to insignificant levels, the uncovered interest parity (UIRP) holds again. We find evidence for a recent regime switch after the SNB has discontinued the exchange rate floor with the Euro.
Keywords: E42; E43; F43; G15; 330; Uncovered Interest Rate Parity (UIRP); Swiss Interest Rate Anomaly; Error Correction; Heteroscedasticity; Markov Regime Switching